Dinâmica de uso e ocupação do solo, aptidão agrícola das terras e perdas de solo em Irupi-ES - Pereira, Eldelon de Oliveira (2023)
The municipality of Irupi is located in the south of the State of Espírito Santo, Caparaó microregion. The site has high vulnerability to soil loss, mainly due to moderate - high rainfall erosivity and the predominance of crops as the main land cover (>50% of the territory), most of which (77%) are cultivated on steep to hilly terrain (slopes between 20 and 75%). In these cases, the overuse of the soil tends to intensify sediment and water losses. Thus, the objective of the work was to determine the changes in land use and land cover that occurred between 2008 and 2020, evaluate the agricultural aptitude of the land (SAAT) and estimate soil losses with the Universal Soil Loss Equation Revised (RUSLE) in Irupi-ES. According to the SAAT, the main factors restricting land use were the low natural fertility of the soils, high susceptibility to erosion and strong impediment to mechanization. About 26.2% of the territory has good, regular or restricted aptitude for farming, 51.2% has restricted aptitude for planted pasture, 15.2% has restricted aptitude for use with forestry and/or natural pasture and 7.5% are lands without agricultural aptitude and destined for the preservation of fauna and flora. To obtain sediment loss estimates with RUSLE, fixed values of the soil cover factor (C) are traditionally adopted for each of the land use and occupation classes. However, especially in the vegetation classes, oscillations in the intensity of the soil cover can be registered, with an effect on the greater or lesser susceptibility to erosion. Thus, the re-scaled NDVI vegetation index was employed as the second method (Adapted Method) to estimate the value of the C-factor in order to make the surface representation of the study area more reliable. The adaptation of NDVI as the C-factor of RUSLE provided satisfactory results. Thus, about 73% of the area of the study region presented vulnerability to water erosion classified as moderate to high (5-25 Mg ha-1 year-1 ), according to the adapted RUSLE model. For the traditional method, 29.5% of the area was classified as slightly vulnerable (0-2.5 Mg ha-1 year-1 ) and 45% as very high (25-100 Mg ha-1 year-1 ).